Expression of the nonclassical HLA-G and HLA-E molecules in laryngeal lesions as biomarkers of tumor invasiveness - Silva, Tarsia G.; Crispim, Janaina C. O.; Miranda, Fabiana A.; Hassumi, Marcela K.; Mello, Julia M. Y. de; Simoes, Renata T.; Souto, Francisco; Soares, Edson G.; Donadi, Eduardo A.; Soares, Christiane P. [UNESP] (F Hernandez, 2011)
Introduction: HLA-G and HLA-E are two nonclassical class I molecules, which have been well recognized as modulators of innate and adaptive immune responses, and the expression of these molecules in virus infected cells has been associated with subversion of the immune response. Objective: In this study we performed a cross-sectional study, systematically comparing the expression of HLA-G and HLA-E in benign, premalignant and malignant laryngeal lesions, correlating with demographic and clinical variables and with the presence of high-risk and low-risk HPV types. Materials and methods: Laryngeal lesions were collected from 109 patients and stratified into 27 laryngeal papillomas, 17 dysplasias, 10 in situ laryngeal carcinomas, 27 laryngeal carcinomas without metastases, 28 laryngeal carcinomas with metastasis along with their respective draining cervical lymph nodes, and 10 normal larynx specimens. The expression of HLA-G and HLA-E molecules was determined by immunohistochemistry. HPV DNA detection and typing was performed using generic and specific primers. Results: HLA nonclassical molecules showed a distinct distribution pattern, according to the larynx lesion grade. HLA-G expression increased in benign and premalignant lesions, and gradually decreased in invasive carcinomas and in respective draining cervical lymph nodes. Conversely, HLA-E expression increased as far as lesion grade increased, including increased molecule expression in the draining lymph nodes of malignant lesions. Only 17 (15.6%) patients were HPV DNA positive. Conclusions: Overexpression of HLA-E and underexpression of HLA-G appear to be good markers for malignant larynx lesion.
Keywords: HLA-G; HLA-E; Laryngeal lesions; HPV; Biomarkers